Legal status of a minister – member of the council of ministers (Discourse of Law and Administration, 2026)
The article examines the legal status of a minister – member of the Council of Ministers – who does not head a government department (“minister without portfolio”). The research question concerns the legal nature of this office and the scope of its competences under the Constitution of the Republic of Poland and the Act on the Council of Ministers. The study employs the doctrinal (dogmatic) method, analysing binding norms, in particular the Constitution, the Act on the Council of Ministers, attribution regulations issued by the Prime Minister, and the internal rules of the Chancellery of the Prime Minister. The thesis advanced is that, despite formal cabinet membership, a minister without portfolio remains directly subordinated to the Prime Minister, while his or her organisational and decision-making autonomy is limited in favour of the Head of the Chancellery of the Prime Minister. The absence of a dedicated department, administrative apparatus and budget precludes exercising powers typical for ministers in charge of departments. The findings indicate that such a minister primarily carries out tasks assigned by the Prime Minister and performs auxiliary functions requiring cross-government coordination. Although this arrangement enhances flexibility, open-ended attribution clauses and imprecise delineation of competences may lead to overlaps and a diffusion of responsibility within government administration.
Keywords: Legal status of the minister; Member of the Council of Ministers; Chancellery of the Prime Minister; Act on the Council of Ministers; Prime Minister